Taking Sides on Severed Heads: Kristeva at the Louvre - Jasper, Alison (Text Matters: A Journal of Literature, Theory and Culture, 2014)
The theorist and philosopher Julia Kristeva is invited to curate an exhibition at the Louvre in Paris as part of a series-Parti Pris (Taking Sides)- and to turn this into a book, The Severed Head: Capital Visions. The organiser, Régis Michel, wants something partisan, that will challenge people to think, and Kristeva delivers in response a collection of severed heads neatly summarising her critique of the whole of western culture! Three figures dominate, providing a key to making sense of the exhibition: Freud, Bataille, and the maternal body. Using these figures, familiar from across the breadth of her work over the last half a century, she produces a witty analysis of western culture’s persistent privileging of disembodied masculine rationality; the head, ironically phallic, ironically and yet necessarily severed; the maternal body continually arousing a “jubilant anxiety” (Kristeva, Severed Head 34), expressed through violence. Points of critique are raised in relation to Kristeva’s normative tendencies-could we not tell a different story about women, for example? The cultural context of the exhibition is also addressed: who are the intended viewers/readers and whose interests are being served here? Ultimately, however, this is a celebration of Kristeva’s tribute to psychic survivors.